State Aid for the Coal Sector in the European Union: Pre- and post-crisis perspective - Podsiadło Piotr (Naše gospodarstvo/Our economy, 2015)
This article presents the evolution of the conditions of state aid admissibility to the coal industry, starting with legal regulations within the European Coal and Steel Community, the European Community, and now the European Union. The thesis was formulated that, in connection with the expiry on 31 December 2010 of Council regulation No. 1407/2002, on the basis of which the European Commission allowed aid for the national mining industry in different member states in the period before the onset of the financial and economic crisis, the immediate cause of introduction of the next regulation for mining state aid in the form of Council Decision 2010/787/EU on state aid to facilitate the closure of uncompetitive coal mines was the increasing intensity of the aid for the mining industry in recent years.